Acute illness in the athlete - Jaworski, C. A.; Rygiel, V. (Clinics in Sports Medicine, 2019)
Athletes are susceptible to many acute illnesses that can interfere with their ability to train and compete as well as potentially affecting teammates and coaching staff. A solid understanding of the preventive measures, diagnosis, and management of such diseases is paramount in the care of an athletic population.